Thermostability modification of β-mannanase from Aspergillus niger via flexibility modification engineering - Tan, Shundong; Tao, Xiumei; Zheng, Pu; Chen, Pengcheng; Yu, Xiaowei; Li, Ning; Gao, Tiecheng; Wu, Dan (Frontiers in Microbiology, 2023)
Introduction β-Mannanases can hydrolyze mannans, which are widely available in nature. However, the optimum temperature of most β-mannanases is too low to be directly utilized in industry. Methods To further improve the thermostability of Anman (mannanase from Aspergillus niger CBS513.88), B-factor and Gibbs unfolding free energy change were used to modify the flexible of Anman, and then combined with multiple sequence alignment and consensus mutation to generate an excellent mutant. At last, we analyzed the intermolecular forces between Anman and the mutant by molecular dynamics simulation. Results The thermostability of combined mutant mut5 (E15C/S65P/A84P/A195P/T298P) was increased by 70% than the wild-type Amman at 70°C, and the melting temperature (Tm) and half-life (t1/2) values were increased by 2°C and 7.8-folds, respectively. Molecular dynamics simulation showed reduced flexibility and additional chemical bonds in the region near the mutation site. Discussion These results indicate that we obtained a Anman mutant that is more suitable for industrial application, and they also confirm that a combination of rational and semi-rational techniques is helpful for screening mutant sites.